(untitled) (Annals of Medical Research, 2021)
Aim: Intoxication is the development of unwanted effects due to exposure to an agent. We retrospectively investigated intoxication cases requiring intensive care treatment, and aim to present demographics, etiologies and prognoses.Material and Methods: We retrospectively investigated records of 23 patients, who were diagnosed with acute drug intoxication and treated in surgical intensive care unit during January 2013 and January 2014.Results: Data from a total of 23 patients (12 female, 52,5%) were analysed. The mean age of the patients was 26±10 years in women and 37±19 years in men. The reason of acute intoxication was suicide attempt with drugs in twenty patients (87%), bee bites in 2 patients (9%), and alcohol intoxication in one patient (3%). Five patients required mechanical ventilation secondary to respiratory insufficiency for an average of 9.6 days. The overall average duration of intensive care stay was 4.6 days.Conclusion: We conclude that majority of patients requiring intensive care treatment due to acute intoxication were female patients who attempted suicide and these patients required a very short duration of follow-up. We are in the opinion that follow-up quality of these patients and clinical management of intensive care units may benefit from periodical retrospective analysis of acute intoxication cases.Keywords: Intensive Care; Intoxication; Suicide.